GEOLOGI DAN PEMODELAN RESERVOIR STATIS 3D PADA FORMASI TALANG AKAR, LAPANGAN TPS, CEKUNGAN SUMATERA SELATAN - Perdana, Septiani
TPS Field is an oil field that is located administrively in South Sumatera Province, and covering an area of aproximately 8880 km2. Geologically, TPS Field located in Tertiarry aged-South Sumatra Basin. This study focus on Talang Akar Formation with two reservoirs interval consisting sandstones as its lithology. The purposes of this study are determinating geological model and estimating remaining reserve from the two reservoirs. Data used in this study are wireline log, seismic 3D, description of cuttings, biostratigraphy reports, and well completion data. There are several methods used in this study, such as well data analysis, seismic data analysis, static reservoir modeling, and the estimation of original oil in place (OOIP). Analysis of cuttings description and their groupings yield five lithofasies Medium to Coarse Sandstone (Smc), Very Fine to Medium Sandstone (Svftm), Fine to Coarse Sandstone (Sm), Sand-Silt-Mud (Fl), and Silt-Mud (Fsm), with facies association in the form of fluvial channel which is potentially become a reservoir zone and floodplain as non-reservoir zone. The depositional environment of research interval is braided to low sinuosity river trending NNE - SSW. Structural geology analysis of the study area shows a normal fault and anticline with NNE - SSW orientation. Static 3D reservoir modelling including structural, facies, and petrophysical modelling performed to determine the reservoir geometry, property distribution, and the estimation of hydrocarbon reserves. The estimation of original oil in place (OOIP) from the two reservoirs is 622 thousand stock tank barrels (MSTB).